Mystics as a Product of Cultural Tourism (On the Example of Georgia’s Archeology) - Maka Piranashvili; Lamara Kadagidze (European Scientific Journal, ESJ, 2017)
Tourism is one of the biggest industries in the world the growth of which in a certain country is strongly stipulated by the internal stability, safe environment and an acceptable level of economic development. Orientation on the promotion of tourism requires the implementation of activities ensuring protection of historical, religious and archeological monuments; care of local folklore, traditions and customs and preservation of art and cuisine. Many countries of the world have started offering intangible resources such as myths, legends and mystics in general as tourist products. Using myths and legends as intangible tourist resources to promote tourism in Georgia has great prospects since according to the world experience and researches in psychology; it increases the interest level and motivation to visit a certain destination on both international and domestic levels. Alongside its cultural and historical resources Georgia is notably rich in myths, legends and mystical diversity enabling cultural-mystical tourism to be pushed forward. Georgia is distinguished with its variety of mystical sights. One can often witness a bunch of tourists gathered around local elderly striving to find out weird stories about a travel destination notwithstanding a language barrier; thus proving that tourists need memorable bizarre stories to connect to the destination site/s emotionally. The article focuses on three archeological monuments of Georgia (Mount Khvamli, Grakliani Hill and Vani Settlements) considered to be a treasure of the world cultural heritage in terms of architecture, history of writing, models of community life, crafts or unique samples of folklore; and concentrates on the significance of the mystics related to each discovery on the monuments as the means to promote cultural tourism in Georgia.